Mobile payment value networks: designing a collaboration tool to approach key partnership issues. (2015) - Dennehy, Denis; Adam, Frederic; Carton, Fergal
Over the past decade, the mobile payment (m-payment) phenomenon has been approached by researchers from diverse backgrounds, each providing a new perspective to this complex topic. Yet, the search for a universal m-payment solution remains elusive. The authors have adopted a design science research approach as it is a problem solving research paradigm that seeks to design and evaluate innovative artefacts with the desire to improve an environment. By adopting a design science research approach, a collaboration tool in the form of a Partnership Management Canvas (PMC) is designed and evaluated through a series of focus groups with over eighty practitioners. The PMC provides practitioners with a common platform that enables them to approach key partnership issues when forming of an m-payment value network. As design science research is a research paradigm that is frequently misunderstood and even resisted by some researchers, it is logical that the paper commences by clarifying what is design science research.